Proses Pembuktian dalam Tindak Pidana Pembunuhan yang Dilakukan Istri terhadap Suaminya (Studi Pada Polrestabes Medan Terkait Putusan No. 907/Pid.B/2020/PN.Mdn) - Benni Ardinal; Maswandi Maswandi; Wessy Trisna (Mahesa Research Center, 2022)
The purpose of this study was to examine the responsibility and process of proving the wife as the perpetrator of the crime of murdering her husband at the Medan Polrestabes regarding the decision no. 907/Pid.B/2020/PN.Mdn. The type of research is normative juridical law, namely normative legal research on legal principles. To prove the act that is charged to a defendant in a belief that the defendant is really guilty, the court conducts an examination process known as proof. Article 184 paragraph (1) of the Criminal Procedure Code has regulated the evidence that is recognized as valid in the trial, namely in the form of witness testimony, expert testimony, letters, instructions, and statements of the defendant. The results of the study indicate that the responsibility of the defendant Zuraida Hanum, has been legally and convincingly proven guilty of committing a crime. Premeditated Murder Committed Together, as charged in the Public Prosecutor's Primary Indictment, sentenced the defendant to the death penalty. The proof process is to check the crime scene, carry out an investigation into the discovery of the corpse, the Police to make a Model A Police Report, the Medan Police to receive an abundance of police reports from the Kutalimbaru Police, the disposition of the police report is received by the assistant investigator Bripka Okma Brata, to complete the mindik (letters), calling witnesses, checking CCTV from the victim's house until the scene of the corpse is found, conducting pre-reconstruction at the house of the murder victim.